Sprint kayaker's kinetic asymmetries at increasing stroke rates - Miller, K. B.; Goreham, J.; Frayne, R. J.; Ladouceur, M. (ISBS Proceedings Archive (Michigan), 2022)
Kinetic movement asymmetries are known to affect factors of performance, increase the likelihood of injury, and to decrease with increased cadences. The aim of this study was to determine if stroke rate affects asymmetry indexes (ASI) in the kayak ergometer footboards and seat. A significant main effect of stroke rate was found on footboard mediolateral total stroke cycle impulse (TSI) ASI (p<0.005) where asymmetry index increased with stroke rate, footboard anteroposterior TSI ASI (p<0.005) where an inverted U-shaped relationship was found with stroke rate, and footboard roll total stroke cycle angular impulse (TSAI) ASI (p<0.001) where an inverted U-shaped relationship was found with stroke rate, and seat mediolateral TSI ASI (p<0.05) where it decreased with stroke rate. The results of this study show that footboard and seat lateral forces counteract each other.